Recombinant perlecan domain V covalently immobilized on silk biomaterials via plasma immersion ion implantation supports the formation of functional endothelium - Lau, Kieran (2024)
Strategies to promote rapid formation of functional endothelium are required to maintain blood fluidity and regulate smooth muscle cell proliferation in synthetic vascular conduits. In this work, we explored the biofunctionalization of silk biomaterials with recombinantly expressed domain V of human perlecan (rDV) to promote endothelial cell interactions and the formation of functional endothelium. Perlecan is essential in vascular development and homeostasis and rDV has been shown to uniquely support endothelial cell, while inhibiting smooth muscle cell and platelet interactions, both key contributors of vascular graft failure. rDV was covalently immobilized on silk using plasma immersion ion implantation (PIII), a simple one-step surface treatment process which enables strong immobilization in the absence of chemical cross-linkers. rDV immobilization on surface-modified silk was assessed for amount, orientation, and bio-functionality in terms of endothelial cell interactions and functional endothelial layer formation. rDV immobilized on PIII-treated silk (rDV-PIII-silk) supported rapid endothelial cell adhesion, spreading, and proliferation to form functional endothelium, as evidenced by the expression of vinculin and VE-cadherin markers. Taken together, the results provide evidence for the potential of rDV-PIII-silk as a biomimetic vascular graft material.